The changing nature of graduate roles and the value of the degree. Issue 2 (4th March 2021) - Jackson, Denise
ABSTRACT: This study explores industry perspectives on the changing nature of graduate roles and the importance of the undergraduate degree, and any impact these have on traditional non-graduate roles in different sectors and industries. Amid declining labour markets, it is critical to consider graduate pathways to employment and the implications of increasing numbers entering non-graduate roles on expectations and turnover. Ongoing disequilibrium in many areas of the graduate labour market points to developing our understanding of alternative pathways into professional roles beyond the undergraduate degree. Interviews were conducted with twenty-one industry members involved in recruiting and/or supervising new graduates. Findings affirmed overeducation among new recruits, highlighting the need for more transparency on employment prospects to prospective higher education students. While there has been extensive research exploring employer perceptions on graduates' preparedness for employment, there has been less consideration of alternative, developmental pathways into entry-level roles to collectively improve youth employment prospects.